2010
DOI: 10.1109/tns.2010.2045768
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Hardness of ${\rm TiO}_{2}$ Memristive Junctions

Abstract: SemiconductingTiO 2 displays non-volatile multi-state, hysteretic behavior in its -characteristics that can be exploited as a memory material in a memristive device.We exposed memristive TiO 2 devices in the on and off resistance states to 45 Mrad(Si) of 1-MeV gamma radiation and 23 Mrad(Si) of 941-MeV Bi-ions under zero bias conditions and none of the devices were degraded. These results suggest thatTiO 2 memristive devices are good candidates for radiation hard electronics for aerospace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 18 publications
3
33
0
Order By: Relevance
“…While substantial research has been carried out on radiation effects in FeRAMs [18], [19], MRAMs [20], [21], and PCRAMs [22], [23], only a few reports on radiation response of ReRAM devices have been published. These include studies on TiO -based memristors [24] and our recent work on Cu-doped-HfO ReRAMs [12], [25].…”
Section: Introductionmentioning
confidence: 99%
“…While substantial research has been carried out on radiation effects in FeRAMs [18], [19], MRAMs [20], [21], and PCRAMs [22], [23], only a few reports on radiation response of ReRAM devices have been published. These include studies on TiO -based memristors [24] and our recent work on Cu-doped-HfO ReRAMs [12], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Tong et al reported experimental results indicating that on-and off-state resistances exhibited only minor changes after exposures to either Co -rays or 941-MeV Bi-ions [6]. For the -ray experiments, the on-state resistance of the devices showed virtually no change after irradiation, and the off-state resistance increased slightly from 22 k to 23 k after 45 Mrad(Si) of total ionizing dose.…”
Section: Impact Of Alpha Particles On the Electrical I Introductionmentioning
confidence: 99%
“…Even with just a few hundreds of memristors, we were able to build a PPUF which will take several years for an attacker to simulate. Furthermore, the developed nano-PPUF is more robust to changes in temperature then CMOS devices [14] and is rad-hard as memristors characteristics are not affected by radiation [15].…”
Section: Discussionmentioning
confidence: 99%